Reflexive games as a kind of social interaction - Shuloshnikova, Maryna (Actual Problems of Mind, 2017)
The author analyses some practical applications of reflexive games and concludes that introducing reflexivity into the structure of social interaction may be of use in overcoming some destructive processes connected to the game character of the social interaction.